2021
DOI: 10.1177/17562848211023386
|View full text |Cite
|
Sign up to set email alerts
|

Real-world effectiveness of vedolizumab in inflammatory bowel disease: week 52 results from the Swedish prospective multicentre SVEAH study

Abstract: Background: Prospectively and systematically collected real-world data on vedolizumab are scarce. We aimed to assess the long-term clinical effectiveness of vedolizumab in inflammatory bowel disease (IBD). Methods: This study was a prospective, observational, multicentre study. Overall, 286 patients with active IBD were included (Crohn’s disease, n = 169; ulcerative colitis, n = 117). The primary outcomes were clinical response at week 12 and clinical remission at week 52, based on the Harvey Bradshaw Index an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
2
19
1
Order By: Relevance
“…Drug persistence was high with 95.5% of patients remaining on treatment after 6 months, and 88.5% after 12 months. These numbers are in line with those reported for IV vedolizumab treatment, ranging from 60–95% after 12 months 25–27 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Drug persistence was high with 95.5% of patients remaining on treatment after 6 months, and 88.5% after 12 months. These numbers are in line with those reported for IV vedolizumab treatment, ranging from 60–95% after 12 months 25–27 …”
Section: Discussionsupporting
confidence: 90%
“…These numbers are in line with those reported for IV vedolizumab treatment, ranging from 60-95% after 12 months. [25][26][27] Our evaluation of the outcome of the switch included thorough investigations of clinical disease activity, applying two activity indices for CD (patient-based HBI and PRO2-CD) and two for UC (SCCAI and PRO2-UC), analysed by both median values and by proportions of patients in remission. All of these analyses corroborated the faecal calprotectin data, showing either unchanged disease activity levels after the switch in both CD and UC patients, or as in the case of SCCAI levels, a statistically significant improvement.…”
Section: Discussionmentioning
confidence: 99%
“…However, in these studies, not all patients were anti-TNF-experienced, and the primary outcome was clinical remission defined as a partial Mayo score <2. 15,16 In one German cohort, with patient characteristics and inclusion criteria similar to this cohort, a lower corticosteroid-free clinical remission rate was found (22%). 17 Few real-world studies described effectiveness of tofacitinib up to 52 weeks of treatment.…”
Section: Discussionmentioning
confidence: 77%
“… 10 According to the systematic reviews of the available real-world experience studies with vedolizumab, which were published in 2018, clinical response rates at week 52 were at the level of 48% (two studies, CI was not calculated) and 52% (16 studies, 95% CI: 37–65%), while clinical remission was achieved in 39% (two studies, CI was not calculated) and in 42% of patients (corticosteroid-free clinical remission assessed in nine studies, 95% CI: 31–53%). 22 , 23 In the more recent long-term real-world studies, the observed clinical response rate was 49% in a Swedish cohort 24 and 45% in an Israeli cohort. 25 In the abovementioned cohort studies, clinical remission rates were 47% and 33%, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…This percentage was similar to that of other studies, where the discontinuation rate after 3-month therapy varied between 18%, 23.5%, and 26% of UC patients. 24 , 25 , 35 …”
Section: Discussionmentioning
confidence: 99%